Learning English Through Role- Musical Based On Intercultural Awareness (2016)
This research tries to promote foreign language learning through intercultural proposal. The objective of this study is to promote intercultural awareness through role-musical in English learning. The research shows how through role-musical proposal the children of fifth grade can develop communicative competences.